Automation of using Robotic Process Automation (RPA) for Web Scraping - Abdul Rahim, Nur Dianna (IRC, 2020)
The study is conducted for the development of service that uses the Robotic Automation Process (RPA) tools to automate the web scraping. Robotic Process Automation (RPA) is one of technology invented to imitate the human working process so that a repetitive process can be automate, it can be done by the RPA softwares or tools. Web scraping has been known that it is involved the process of data extraction from webpage then exported into many of output forms such as in Microsoft Excell files, Extensible Markup Language (XML) data files, or Comma Separated Values (CSV) files. In this project development, the chapters will cover the literature reviews of different RPA tools used in the industry and which types of RPA tools is recommended for IT and non-IT users. It will includes the methodology and the Gantt chart of project development as well as the result will be discussed at further page. The result will be both discussed in comparison of between the automated process done via RPA and the user manual work process.